2014
DOI: 10.1038/nrgastro.2014.102
|View full text |Cite
|
Sign up to set email alerts
|

Growth problems in children with IBD

Abstract: Crohn's disease in childhood causes linear growth retardation, which has a substantial effect on management of this disease. By contrast, growth is rarely a problem in children presenting with ulcerative colitis. Depending on how growth failure is defined, approximately one-third of children with Crohn's disease have growth retardation at diagnosis. Although corticosteroids can suppress growth, decreased height at diagnosis demonstrates that this finding is a consequence of the disease and not merely an advers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 118 publications
1
45
0
Order By: Relevance
“…This underappreciation is particularly apparent in the context of microbiota‐associated pathologies in human. For example, patients with inflammatory bowel disease (IBD) have digestive problems associated with microbiota diversity, but also experience growth retardation due to impaired GH signaling and delayed sexual maturation . Polycystic ovarian syndrome (PCOS) is an endocrine and metabolic disorder with high testosterone level and also linked to microbiota diversity, perturbed ovarian development, and GH secretion .…”
Section: Disturbed Circadian Clock Gh and Sexual Development: An Unmentioning
confidence: 99%
“…This underappreciation is particularly apparent in the context of microbiota‐associated pathologies in human. For example, patients with inflammatory bowel disease (IBD) have digestive problems associated with microbiota diversity, but also experience growth retardation due to impaired GH signaling and delayed sexual maturation . Polycystic ovarian syndrome (PCOS) is an endocrine and metabolic disorder with high testosterone level and also linked to microbiota diversity, perturbed ovarian development, and GH secretion .…”
Section: Disturbed Circadian Clock Gh and Sexual Development: An Unmentioning
confidence: 99%
“…A study conducted in the early 1980s found that 23% of pediatric cases of IBD showed growth retardation, which was twice as frequent for children with CD [24]. Later, additional studies have shown growth retardation to be most frequent in CD with a frequency of around 10–19% and to rarely manifest in children with UC [25,26,27]. The cause of growth retardation during CD is likely a combination of impaired nutritional uptake and a direct effect of inflammation on the GH-IGF-1 axis resulting in reduced levels of bioavailable IGF-1 [27,28].…”
Section: Inflammatory Bowel Diseasesmentioning
confidence: 99%
“…5 In this study, we aimed at identifying IBD-related parameters that might influence the IGF-1-height relation through a multivariate, structural model analysis (SEM) in children with CD and UC. Insulin-like growth factor-1 (IGF-1), the end hormone of the growth hormone (GH) axis, has been identified as the key determinant of normal linear growth.…”
Section: Introductionmentioning
confidence: 99%